Accessing capital markets: Aristocrats and new share issues in the British bicycle boom of the 1890s. Issue 2 (17th February 2018) - Amini, Shima; Toms, Steven
Abstract: The article reconsiders the mid-1890s boom in which a large number of firms in the bicycle, pneumatic tyre and related industries were floated. It investigates why so many of these issues featured aristocratic directors in their prospectuses and finds that they represented social connections that were a necessary condition for regional industrial firms to gain a London listing. The case shows that the role and value of these directors was to access capital markets and financial resources, as opposed to a temporary aberration designed to inflate share prices and mislead investors.